2012
DOI: 10.1002/mnfr.201100387
|View full text |Cite
|
Sign up to set email alerts
|

Importance of β,β‐carotene 15,15′‐monooxygenase 1 (BCMO1) and β,β‐carotene 9′,10′‐dioxygenase 2 (BCDO2) in nutrition and health

Abstract: In humans, varying amounts of absorbed β-carotene are oxidatively cleaved by the enzyme β,β-carotene 15,15'-monooxygenase 1 (BCMO1) into two molecules of all-trans-retinal. The other carotenoid cleavage enzyme β,β-carotene 9',10'-dioxygenase (BCDO2) cleaves β-carotene at the 9',10' double bond forming β-apo-10'-carotenal and β-ionone. Although the contribution of BCDO2 to vitamin A formation has long been debated, BCMO1 is currently considered the key enzyme for retinoid metabolism. Furthermore, BCMO1 has limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 89 publications
0
63
0
2
Order By: Relevance
“…These findings reveal that retinoic acid negatively regulates BCMO expression via the signaling of RARs and ISX, indicating that regulation occurs in response to diet with a negative feedback mechanism (21,28). BCMO is not only the key enzyme in retinal and retinoic acid production from b-carotene, but it is also active as a regulatory factor of lipid metabolism (29). The promoter region of human and mice BCMO genes contains a peroxisome proliferator response element, and BCMO expression is transcriptionally regulated by PPARg, which is a member of the nuclear superfamily and has a critical role in controlling energy, lipid, and glucose metabolism (30,31).…”
Section: Discussionmentioning
confidence: 83%
“…These findings reveal that retinoic acid negatively regulates BCMO expression via the signaling of RARs and ISX, indicating that regulation occurs in response to diet with a negative feedback mechanism (21,28). BCMO is not only the key enzyme in retinal and retinoic acid production from b-carotene, but it is also active as a regulatory factor of lipid metabolism (29). The promoter region of human and mice BCMO genes contains a peroxisome proliferator response element, and BCMO expression is transcriptionally regulated by PPARg, which is a member of the nuclear superfamily and has a critical role in controlling energy, lipid, and glucose metabolism (30,31).…”
Section: Discussionmentioning
confidence: 83%
“…Beta-ionone (EAFUS/cosmetics) is also formed in animals by beta-carotene oxygenase 2 (BCO2) which converts betacarotene to β-10'-apocarotenal and β-ionone, en route to the synthesis of Vitamin A [254]. It does not activate retinoid receptors RARA or RARB [255] but binds to a retinol binding protein, beta-lactoglobulin B, involved in the oral delivery of retinol to neonates [256].…”
Section: Other Endogenous Compounds Targeting Autism Genesmentioning
confidence: 99%
“…BCO2 (β, β-carotene-9',10'-oxygenase2) is an enzyme that catalyzes the asymmetric cleavage of carotenoids in the inner membrane of mitochondria [15]. Recent controversial research findings demonstrated that BCO2 may not be activated in the human macula where carotenoids preferentially accumulate [16,17], suggesting that BCO2 may not only function as a carotenoid cleavage enzyme which warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%